The first issue of InJAST available in print and online - Dolly Priatna; Kathryn A. Monk (Universitas Pakuan, 2020)
It is our great pleasure to announce that the very first issue of the Indonesian Journal of Applied Environmental Studies (InJAST) is now be available in both print and online. This journal has evolved from the Journal of Environmental Education which started in 2015, and was managed by the Study Programme of Population and Environmental Education, Graduate Programme of Pakuan University. Because this study programme has now become the Study Programme of Environmental Management, we have decided to establish this new journal to publish scientific articles covering broader environmental issues that are written by the Indonesian students of graduate programmes either in Pakuan and other universities or researchers. Meanwhile, the publication and management of the Journal of Environmental Education will be transferred to another relevant faculty or study programme within Pakuan University.We intend the new InJAST to be published in English (with abstracts both in English and Bahasa) so that it can reach a wider readership internationally, and we hope encourage international environmental students and scientists working in Indonesia or on topics of specific relevance to Indonesia, to disseminate their research results and findings through this journal.We are pleased to also announce that it has been agreed in principle that this new journal will be published collaboratively between the Graduate School of Pakuan University and PERWAKU (Perhimpunan Cendikiawan Pemerhati Lingkungan Indonesia, the Indonesian Association of Environmentalist Scholars). A formal Memorandum of Understanding between both parties will be signed in the near future.In this occasion, we, as the chief editors of this new journal, would like to express our gratitude to various parties and individuals who have supported this initiative, especially to Prof. Dr. H. Bibin Rubini, M.Pd. (Chancellor of Pakuan University), Prof. Dr. Ing. H. Soewarto Hardhienata (Dean of Graduate School Pakuan University), and Prof. Jatna Supriatna, Ph.D. (Chairman of PERWAKU Indonesia). We would also like to express special thanks to our national and international colleagues at Pakuan University and elsewhere, who have so generously offered their time as members of the editorial board of the journal.Last but not least, we hope that the Indonesian Journal of Applied Environmental Studies (InJAST) will provide new colour and perspectives the scientific journals published by Pakuan Univeristy, and become the vehicle of choice for environmental science students and scientists to disseminate of their work.